Global and regional estimates of the prevalence of root caries – Systematic review and meta-analysis - Kalyana Chakravarthy Pentapati; Hanan Siddiq; Sravan Kumar Yeturu (Saudi Dental Journal)
Aim: To evaluate the pooled prevalence of root caries through a systematic review and meta-analysis. Methods: A keyword search was done in Scopus, Pubmed and CINAHL databases using all the synonyms of root caries in the published literature (till January 1st, 2018). The search was supplemented with standard Boolean operators and other keywords like prevalence, epidemiology in the title, abstract and MeSH terms. Data was extracted and exported to Covidence software for screening and removal of duplicates. Results: The search revealed a total of 492 documents from Scopus (n = 95), Pubmed (n = 220) and CINAHL (n = 177). Random effects model was used as there was a high degree of heterogeneity was seen among the studies published (I2 = 99.62%). A total of 74 publications were included in the analysis of the pooled prevalence of root caries which yielded a prevalence of 41.5 (36.9–46.1). Conclusion: Root caries is a significant problem, and four out of ten adults might be affected. Keywords: Root, Caries, Decay, Prevalence, Systematic review, Meta-analysis